Germline BAP1 mutations predispose also to multiple basal cell carcinomas. (8th September 2014) - de la Fouchardière, A.; Cabaret, O.; Savin, L.; Combemale, P.; Schvartz, H.; Penet, C.; Bonadona, V.; Soufir, N.; Bressac‐de Paillerets, B.
<x xml:space="preserve">Abstract</x> The BRCA1‐associated protein 1 (BAP1) gene encodes a nuclear deubiquitin enzyme which acts as a tumour suppressor. Loss of function germline mutations of BAP1 have been associated with an enhanced risk of uveal and cutaneous melanomas, mesothelioma, clear cell renal cancer and atypical cutaneous melanocytic proliferations. In two independent BAP1 families, we noticed an unusual frequency of basal cell carcinomas (BCCs). Indeed, 19 BCCs were diagnosed in four patients, either of superficial (13/19) or nodular (6/19) subtype; they were all located in chronic sun‐exposed areas (limbs, head or neck). Immunohistochemistry (IHC) identified in the 19 tumours, complete or partial loss of BAP1 protein nuclear expression, restricted to the BCC nests. A control study was conducted in 22 sporadic BCCs in 22 subjects under 65 without known associated BAP1 tumours: no loss of BAP1 expression was found. Overall, our observations suggest that BCCs are part of the BAP1 cancer syndrome, perhaps in relation with chronic sun exposure and melanocortin 1 receptor (MC1R) variants. In conclusion, cutaneous follow‐up of BAP1 carriers should not only aim to detect melanocytic neoplasms but also BCCs.